2018
DOI: 10.1016/j.bbmt.2018.06.020
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Functional Outcomes after Hematopoietic Stem Cell Transplant for Early Infantile Krabbe Disease

Abstract: Allogeneic hematopoietic stem cell transplantation (HSCT) can retard the progression of early infantile Krabbe disease (EIKD). Superior outcomes are achieved if HSCT is performed before the onset of symptoms; however, little information is available about the long-term outcomes in surviving patients. We now describe functional outcomes in presymptomatic infants who underwent HSCT for EIKD at ≤ 2 months of age. Records of the 19 patients who underwent HSCT for EIKD at ≤ 2 months of age from 1996 to 2010 were re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
65
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(65 citation statements)
references
References 16 publications
(27 reference statements)
0
65
0
Order By: Relevance
“…While GALC should intuitively be required during myelination, many of these temporal events seem to precede the bulk of CNS myelination. Furthermore, patients diagnosed in utero, and treated within the first few weeks of life, do better than patients treated at 1–2 months old 12 , 13 . These findings underlie the necessity for properly defining the precise timepoint in which GALC is first required.…”
Section: Introductionmentioning
confidence: 99%
“…While GALC should intuitively be required during myelination, many of these temporal events seem to precede the bulk of CNS myelination. Furthermore, patients diagnosed in utero, and treated within the first few weeks of life, do better than patients treated at 1–2 months old 12 , 13 . These findings underlie the necessity for properly defining the precise timepoint in which GALC is first required.…”
Section: Introductionmentioning
confidence: 99%
“…NBS for a leukodystrophy known as Krabbe disease (KD) started in New York state in 2006, soon after it was shown that early cord blood transplantation favorably alters the natural history of the disease [ 1 , 2 , 3 ]. NBS for KD was added to additional state panels after New York (Illinois, Indiana, Kentucky, Louisiana, Missouri, New Jersey, New Mexico, Ohio, Pennsylvania, South Carolina, Tennessee), and KD NBS has started in Indiana, Kentucky, Missouri, New Jersey, New York, Ohio, Illinois and Tennessee.…”
Section: Introductionmentioning
confidence: 99%
“…The first five early infantile KD NBS-positive patients in New York state had several factors leading to a delay in treatment, which negatively impacted patient outcomes [ 4 ]. Long-term follow-up of KD patients identified via family history who were treated by hematopoietic stem cell transplantation have been published [ 1 , 7 , 8 ]. Furthermore, new data on treated patients identified through NBS will be reported in the near future, which show improved outcomes since the first eight years in New York.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, psychosine accumulation is neurotoxic and has been reported to facilitate fibrillation of α-synuclein (SNCA) [99,100,103]. There is still no effective treatment for Krabbe disease, but stem cell transplant has been a modality of treatment in some states of the USA [104].…”
Section: Gaucher and Krabbe Diseasementioning
confidence: 99%